Effect of Exercise Volume on Plantar Microcirculation and Tissue Hardness in People With Type 2 Diabetes - Ren, Weiyan; Duan, Yijie; Jan, Yih-Kuen; Ye, Wenqiang; Li, Jianchao; Liu, Wei; Liu, Hongmei; Guo, Junchao; Pu, Fang; Fan, Yubo (Frontiers in Bioengineering and Biotechnology, 2021)
Objective: Exercise has been reported to be beneficial for people with type 2 diabetes (T2DM), but exercise, especially weight-bearing exercise, may increase the risk of diabetic foot ulcers (DFUs). This study aimed to explore the associations between different volumes of weight-bearing physical activities and plantar microcirculation and tissue hardness in people with T2DM. Methods: 130 elderly people with T2DM were enrolled for this cross-sectional study. They were classified into the high exercise volume group and the low exercise volume group based on their weekly energy expenditure (metabolic equivalents per week) in the past year. Weekly energy expenditure was calculated using the International Physical Activity Questionnaire and the Compendium of Physical Activities. The plantar oxygen saturation (SO2) and soft tissue hardness of each participant’s right foot were measured. Results: A total of 80 participants completed the trial. The average exercise energy expenditure of the high exercise volume group and the low exercise volume group were significantly different (p < 0.05). The results showed that the SO2 of the high exercise volume group (67.25 ± 6.12%) was significantly higher than the low exercise volume group (63.75 ± 8.02%, p < 0.05). The plantar tissue hardness of the high exercise volume group was lower than the low exercise volume group in the big toe, midfoot and hindfoot regions (p < 0.05). Conclusion: This study demonstrates that higher volumes of exercise are associated with better plantar microcirculation and lower plantar tissue hardness in people with T2DM. The findings of this study indicate that weight-bearing exercise may not increase risk of developing diabetic foot ulcers.